The Effect of Kahoot as a Learning Media on Students’ Vocabulary Mastery at SD Negeri 7 Kubutambahan - Iswanti, Ni Putu Ratih Ramadhani; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This research was conducted with the aim of determining the influence of the use of Kahoot as a game- based learningmedium on vocabulary mastery in elementary school students. This study uses a quantitative approach with a pre-experimental one-group pretest-posttest design. The subject of this study used a sample of 34 students in class V at SDNegeri 7 Kubutambahan Bali. Vocabulary mastery data was collected through vocabulary tests given before and after the application of kahoot media in English learning. The data of this study was analyzed using descriptive statistics. Inferential analysis in the form of a paired sample t-test. The results of the study showed a significant increase in vocabulary mastery in students after using kahoot as a learning medium in class, with a significance value of p < 0.05. The findings of this study show that kahoot is an effective learning medium and can attract students' attention to improve students'vocabulary mastery in elementary school. Therefore, the use of game-based digital learning media such as kahoot is recommended to support the learning of English vocabulary, especially in elementary schools in semi-rural areas.